Investigation of concrete properties using basalt fiber (Eurasian Journal of Engineering and Technology, 2022)
Modern construction is inextricably linked with the tasks of increasing the efficiency of construction production, reducing the cost and complexity of technological processes, economical use of material and energy resources, the use of new progressive materials